Implementasi Sistem Keuangan Desa (SISKEUDES) Pemerintah Desa Kecamatan Blambangan Umpu Kabupaten Way Kanan Provinsi Lampung - Ani Heryani; Ribkha Kamizona (Universitas Bandar Lampung (UBL), 2023)
This study aims to examine the implementation of the Village Finance System in the Village Government of Blambangan Umpu District and the factors influencing it. Qualitative research methods were used to accomplish this goal by analyzing the data descriptively. The data collection techniques involved observations, interviews, and documentation. The study revealed that the reporting of village funds implementation could be assessed from various indicators. (1) The available facilities and infrastructure to support the job are suboptimal due to limitations in their capacity to accommodate the work. (2) The process and reporting in the management of village funds by the village government in Blambangan Umpu District, Way Kanan Regency, do not comply with established regulations, rendering the government ineffective in their management. (3) Financial Report on Village Fund Output in Blambangan Umpu District, Way Kanan District, reveals inaccuracies and input errors. Factors affecting financial reporting of village funds comprise of supportive and inhibitory factors. Supporting factors include training and socialization of the village funds system, whereas inhibitory factors comprise of human resources and timeliness issues.